Assessing Devolution in the Canadian North: A Case Study of the Yukon Territory - Alcantara, Christopher; Cameron, Kirk; Kennedy, Steven (Scholars Commons @ Laurier, 2012)
Despite a rich literature on the political and constitutional development of the Canadian territorial North, few scholars have examined the post-devolution environment in Yukon. This lacuna is surprising since devolution is frequently cited as being crucial to the well-being of Northerners, leading both the Government of Nunavut and the Government of the Northwest Territories to lobby the federal government to devolve lands and resources to them. This paper provides an updated historical account of devolution in Yukon and assesses its impact on the territory since 2003. Relying mainly on written resources and 16 interviews with Aboriginal, government, and industry officials in the territory, it highlights some broad effects of devolution and specifically analyzes the processes of obtaining permits for land use and mining. Our findings suggest that devolution has generally had a positive effect on the territory, and in particular has led to more efficient and responsive land use and mining permit processes.